La construction d’un positionnement par les cadres de proximité : expérience et encadrement dans un service public - Cécile Piney; Corinne Gaudart; Adelaide Nascimento; Serge Volkoff (Perspectives Interdisciplinaires sur le Travail et la Santé)
In the public service, performance-based management is spreading, reforms are following one after the other, and the work of managers like that of client service agents is changing continually. The ways of integrating performance-based management vary in terms of how performance, work well done, service provided to the user, and the use of indicators are defined. In the restrictive framework of performance-based management, first-line managers receive orders before in turn influencing employees, and must adopt a position between prescribed work, measured work, and real work. Depending on their experience, the distance they take with regard to performance-based management on the one hand and, on the other, the client service agents’ real work varies. The objective of this study is to characterize the work activity of first-line managers and the impact of a management method on work conditions. The proposed qualitative analysis is based on an examination of the managers’ work activity: 12 interviews with first-line managers, followed by open and systematic observations of 8 other first-line managers with different careers and supervisory structures in a French administration service.